Global Strategies to Enhance Higher Education Participation: Lessons from ASEAN and Beyond in Addressing Enrollment Challenges and Workforce Demands - Dwi Putri Pramesti, Ginna Novarianti; Dwi Savandha, Septien; Amelia, Amelia (Cakrawala Repositori IMWI, 2025)
Widening access to higher education remains a global priority, particularly for regions facing socioeconomic disparities and labor market misalignments. In the ASEAN region, enrollment challenges and workforce demands continue to pose significant obstacles to inclusive and effective higher education systems. This study aimed to explore global and regional strategies that enhance higher education participation and align educational outcomes with workforce needs, specifically focusing on rural and village-based contexts. Using a qualitative comparative design, the study analyzed 25 policy documents and 30 peer-reviewed articles from ASEAN countries and globally. Data were collected through structured document analysis and coded thematically to identify key trends in policy instruments, institutional innovations, digital learning pathways, and international cooperation. The findings reveal that countries achieving high participation and employability rates implement targeted financial aid, flexible learning models, industry-academic collaboration, and decentralized management systems. However, in many ASEAN states, these strategies have yet to reach rural communities due to infrastructural and managerial limitations. This study contributes a novel framework that links higher education participation to village development through adaptive education management and localized workforce integration. The results underline the need for inclusive, context-sensitive policy reforms and institutional accountability mechanisms to ensure sustainable impacts. Practical implications include strengthening local education governance and expanding access to digital and vocational programs in underserved areas.